Byessonov N. Y. Semantic types of constructions with causative linking verbs in English - Byessonov N. Y. (Philological Treatises, 2020)
The article deals with semantic peculiarities of constructions with causative linking verbs in English. The semantics of causative linking verbs as the main components expressing causative relations in causative constructions has been considered. The formulae interpreting their meaning have been suggested as well as the classification of the constructions under study according to their semantic types. The productivity of the semantic types in question has been determined.